RELASI SOSIAL, PERAN USAHA, SANKSI DAN SISTEM ONLINE TERHADAP KEPATUHAN PAJAK RESTORAN DI MALANG: Relasi Sosial, Peran Usaha, Sanksi, Sistem Online, Kepatuhan Pajak Restoran - Handayanto, Adrian Junaidar; Wibisono, Sukarno Himawan; Mukoffi, Ahmad; As’adi, As’adi; Sularsih, Hermi; Handayani, Sartina (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
The purpose of this study was to examine the effect of social relations, business roles, sanctions, and online systems on restaurant taxpayer compliance in Malang City. The sample used was 93 taxpayers. Data collection in the study using a questionnaire with multiple linear regression data analysis techniques. The results of the study are social relations, company functions, sanctions, and online systems all have a big impact on restaurant tax compliance in Malang City. Social relations for restaurant taxpayers, both in the form of social support and information sharing, can increase the level of tax compliance. Companies also play an active role in ensuring the tax compliance of restaurant taxpayers. Administrative and criminal sanctions play a major role in increasing restaurant taxpayer compliance. ease of access through online payment methods also plays an important role in increasing tax compliance. In order to improve restaurant tax compliance in Malang City, initiatives that build social interaction, the role of the business world, apply appropriate sanctions, and improve accessibility through online platforms can be developed and implemented.